Exploiting Hypertext’s Potential for Teaching Gender Studies - Maya Zalbidea Paniagua (Texto Digital)
The aim of this article is to show what feminist electronic literature can contribute to the study of gender theories and feminist literature. The study of feminist hypertext fictions and the use of hypertext as a teaching tool are facilitated by the intrinsic characteristics of the electronic medium, complementing the electronic medium and providing alternative possibilities in the learning process: collaborative authorship, multivocality, textual openness, non-hierarchical and rhizomatic structures, neo-kathartic effects and open publishing. Teaching feminist electronic literature using the hypertext offers the possibility of updating and discussing gender through a medium that permits rearranging the hypertext, better organized analyses of intertextuality and fostering the study through association and connections, which is the way the human brain works. The teaching method proposed pursues the objective of studying narratives about gender taking advantage of the new technologies without losing dialogues in class as intuitive learning process.